Asylum appeal hearing observations at First-tier Tribunal hearing centres in the UK, 2013-2016 - Gill, Nick (UK Data Service, 2019)
Quantitative collection of observations of 240 First-Tier Tribunal (Immigration and Asylum Chamber) substantive asylum appeal hearings and 50 First-Tier Tribunal (Immigration and Asylum Chamber) substantive Detained Fast Track asylum appeal hearings in the UK. For each individual hearing, observations of 809 and 889 variables resp. were recorded. The data collection contains two versions with different access conditions: a version available to registered users (RUO) containing 91 and 46 cases; and a closed version (CA) of all cases for which access can be requested from the depositor. During the research also qualitative data were collected: ethnographic research diaries completed by researchers who observed around 100 asylum appeal hearings from the public gallery of the tribunal rooms; and interviews with asylum appellants, clerks, interpreters, friends of appellants, and legal actors. These data are not included here. When asylum seekers' claims for asylum get refused they often appeal in front of an immigration judge at a hearing centre that is part of the First-tier Tribunal (Immigration and Asylum Chamber). Little academic work has examined how these hearings are conducted in practice. Are they conducted consistently, for example, and if not how do they vary? While aggregate data on outcomes (that is, the decisions of judges) can be obtained by court, no record of the happenings during these hearings is made publicly available. As a result a clear view of the procedures of the tribunal, and hence of procedural justice, remains obscured. This project examined in detail what happens during asylum appeal hearings through ethnography, interviews and via a survey. In so doing it aims to explore the degree to which process varies according to a number of factors including the location of hearings, the scheduling of the case, the gender of appellant and judge and whether the appellant is unrepresented. Alongside these specific questions, the data deposited here - which is derived from the survey-based part of the project - offers a unique view onto a legal process that it rarely examined in detail from the perspective of what actually happens during the hearings.